The Islam Wasathiyah of KH. Abdurrahman Wahid in the Islamic Political Arena - Raha Bistara; Fuady, Farkhan (Journal of Islamic Civilization, 2022)
Indonesia as a pluralistic country and has a variety of cultures, ethnicities, races, religions and so on. Making it a pluralistic country and it is important to maintain the unity and integrity of the nation. In dealing with the plurality of the Islamic concept of wasathiyah, it is important to implement it today. Moreover, political issues, especially Islam, will be more complex. Seeing this, Abdurraman Wahid as a Muslim scholar paid attention to creating an atmosphere of peace in the midst of differences. By using qualitative methods and library research approach. This means that this research is a library research, where the data source comes from the library. The analysis used is descriptive and historical analysis, it is useful to provide a clearer picture of the concept of Islam wasathiyah Abdurrahman Wahid. The results of this study found that Abdurrahman Wahid argued that Washatiyah Islam was middle, not extreme. Meanwhile, Abdurrahaman Wahid's Islamic politics is also very relevant to be applied in Indonesia. Even though Indonesia is a plural country that has various religions. To achieve moderate and fair conduct in the life of the nation and state is a mandatory requirement in efforts to maintain peace in Indonesia in particular and world peace in general. Indonesia sebagai negara yang majemuk dan memiliki berbagai macam budaya, suku, ras, agama dan lain sebagainya. Menjadikanya negara yang plural dan penting untuk menjaga kesatuan dan persatuan bangsa. Dalam menghadapi kemajemukan konsep Islam wasathiyah menjadi penting untuk di implementasikan dimasa sekarang. Telebih lagi mengenai permasalahan politik khususnya Islam akan lebih kompleks. Melihat tersebut Abdurraman Wahid sebagai cendekiawan muslim memberikan perhatian untuk menciptakan suasana damai ditengah perbedaan. Dengan menggunakan metode kualiatif dan pendekatan library reaserch. Berarti penelitian ini merupakan penelitian pustaka, yang mana sumber data bersumber dari pustaka. Analisis yang digunakan adalah analisis deskriptif dan historis, hal tersebut berguna untuk memberikan gambaran yang lebih jelas mengenai konsep Islam wasathiyah Abdurrahman Wahid. Hasil penelitian ini menemukan bahwa dipaparkan Abdurrahman Wahid berpendapat bahwa Islam washatiyah merupakan tengah-tengah, tidak bersikap ektrim. Sedangkan Gagasan politik Islam Abdurrahaman wahid juga sangat relevan diterapkan di Indonesia. Walaupun Indonesia sebagai negara plural yang memiliki berbagai agama. Sehingga bersikap moderat dan berlaku adil dalam hidup berbangsa dan bernegara menjadi syarat wajib dalam upaya menjaga perdamaian di Indonesia khususnya dan perdamaian dunia pada umumnya.